P30 Blood pressure and grip strength at age 61–63 in the Newcastle Thousand Families birth cohort. (26th August 2022) - Pearce, Mark; Townend, Georgia; Smith, Josie; Slack, Emma
Abstract : Background: Current research surrounding the association between blood pressure (BP) variables and grip strength is limited and very inconsistent. The majority of studies show a negative association, with decreased blood pressure associated with increasing grip strength, with the minority observing a positive association. The inconsistency of these findings suggests further research is needed to establish whether there is a true positive or negative association. Methods: The Newcastle Thousand Families Study is a birth cohort established in Newcastle upon Tyne in 1947. Data have been collected, mostly prospectively, at various points throughout their lives. At age 61–63 years, a follow up attended by 350 members of the original cohort, included measurements of BP (systolic and diastolic blood pressure, and pulse) and grip strength. These data, along with potential confounders, such as BMI and sex collected at the same time, or previously, were analysed using multivariable linear regression, with fractional polynomials used to assess the non-linearity of any associations. Results: No significant associations were seen between grip strength and either systolic or diastolic blood pressure. A significant association was seen between in BMI adjusted linear regression for grip strength and pulse [Coefficient= -0.106 (95%CI -0.202 to -0.009) P=0.032)], with the fractional polynomial models suggesting non-linearity. No significant interactions were observed between BP variables and sex. Discussion: No significant associations were seen between grip strength and BP variables in this cohort, apart from pulse, for which there was a non-linear association. Future research may involve a larger sample size to increase statistical power and assessments at different ages to observe the effect of age on any associations. If a positive association were to be true, this could promote interventions aimed at reducing hypertension rates that may also reduce frailty through reducing the decrease in grip strength as people age.